The effects of different natural environment influences on health and psychological well-being of people: a case study in Selangor - Raman, Thivya Laxshmy; Abdul Aziz, Nor Akmar; Yaakob, Sam Shor Nahar (Multidisciplinary Digital Publishing Institute, 2021)
Background: People benefit from the recreational services provided by an urban corridor, urban park, and urban forest. Due to ongoing land-use interest and urban development, however, these natural environments are coming under increasing pressure. Simultaneously, the world is becoming increasingly urbanised, and living in cities has been linked to mental health issues. On the other hand, different natural environments are known to create healthier environments, and the need for effective restorative environments has never been greater. The purpose of the study was to compare the impacts of walking in different natural environments. Methods: I) Kota Damansara Community Forest Reserve, II) Mutiara Damansara Recreational Park, and III) the Urban Green Corridor along Jalan PJU 7/2 were used as control study sites in this study. Each site was visited only once by the study participants (40 women and 40 men). Walking for 30 min was a part of the experiment. To identify the psychological effects of different natural environments, the Depression, Anxiety, and Stress Scale (DASS21), Profile of Mood States (POMS), Positive and Negative Affect Schedule (PANAS), and Restoration Outcome Scale (ROS) were utilised. Results: In all three natural environments, the restorative effects were found to increase significantly. Conclusion: The overall conclusion of the field experiment is that being in an urban green corridor can also provide a refreshing environment. In terms of stress reduction among working adults, the recreational park is sufficient, while urban-forested areas are more effective in improving mental health by minimising stress, anxiety, and depression.